2016
DOI: 10.1111/papr.12461
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonsteroidal Anti‐Inflammatory Drugs for Symptomatic Treatment of Episodic Headache

Abstract: Nonsteroidal anti-inflammatory drug use in headache was higher than could be hypothesized based on guidelines, with NSAID preferences not entirely coinciding with international recommendations. This outcome suggests the need for greater awareness of all treatment options in headache by both patients and physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…In the current study, 45.5% of the patients took simple analgesics (i.e., paracetamol) and 54.5% took NSAID particularly ibuprofen. These data are similar to those previously reported by Affaitati et al [10] and also agree with the recommendations from international guidelines [5]. Individuals with lower frequency of headaches, that is, those with more episodic attacks, tend to use symptomatic medication in a greater proportion than those with CTTH.…”
Section: Symptomatic Medication In Tthsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, 45.5% of the patients took simple analgesics (i.e., paracetamol) and 54.5% took NSAID particularly ibuprofen. These data are similar to those previously reported by Affaitati et al [10] and also agree with the recommendations from international guidelines [5]. Individuals with lower frequency of headaches, that is, those with more episodic attacks, tend to use symptomatic medication in a greater proportion than those with CTTH.…”
Section: Symptomatic Medication In Tthsupporting
confidence: 91%
“…In our study, 81% of our sample of patients with TTH reported taking medication for their headache attacks, data similar to a recent study conducted in Italy where 90% of individuals with TTH were symptomatic medication users [10]. In the current study, 45.5% of the patients took simple analgesics (i.e., paracetamol) and 54.5% took NSAID particularly ibuprofen.…”
Section: Symptomatic Medication In Tthsupporting
confidence: 90%
See 1 more Smart Citation
“…In 2011, Sumelahti et al analyzed prescription patterns for migraine treatment in Finland and discovered that nonsteroidal anti‐inflammatory analgesics were more frequently given to patients than triptans, although the use of preventive medication was very common among individuals suffering from migraine. These results were recently corroborated by Affaitati et al, who estimated that 80% of migraine patients use nonsteroidal anti‐inflammatory drugs for the treatment of their headache. Nonetheless, medication costs were not available in these 2 studies, so they were not able to shed light on the economic aspects of migraine treatment in Europe.…”
Section: Introductionsupporting
confidence: 56%
“…Afterwards, researchers' attention was driven towards comparing the effectiveness of the seven triptan brothers, alone or in combination with NSAIDs. The debate revolved around safety, efficacy, consistency, drugdrug interactions with prophylactic drugs, pharmacokinetics/ pharmacodynamics, new delivery pathways, extension of this pharmacological class to the population aged under 18 or over 65 years, evaluation of common adverse events, disability levels [6][7][8][9][10][11][12]. Notwithstanding, only 27% of migraine patients receive a correct diagnosis and only 17% of them takes triptans for a crisis [13,14].…”
Section: Travelling From Nsaids To Triptans To Cgrpmentioning
confidence: 99%